2017
DOI: 10.1080/02134748.2016.1248025
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and criterion validity of the Perceived Vulnerability to Disease Scale (PVD) in the Spanish population / Propiedades psicométricas y validez de criterio de la escala de Percepción de Vulnerabilidad a la Enfermedad (PVE en población española)

Abstract: Perceived Vulnerability to Disease may be defined as the beliefs about personal susceptibility to the transmission of infectious diseases and the emotional discomfort associated with the potential disease transmission. To evaluate these beliefs, the Perceived Vulnerability to Disease Scale (PVD) has been used in most studies. The aim of Study 1 was to validate the PVD questionnaire to the Spanish population. The sample was made up of 744 university students from all over Spain. Confirmatory factor analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Items are scored on a 7point Likert scale, with endpoints labelled as "strongly disagree" and "strongly agree". The PVD has performed well on tests of reliability and validity (Duncan et al, 2009;Díaz et al, 2016;Magallares et al, 2017;Diaz, Beleña, & Zueco, 2020). In the present study, two items were excluded which appeared to be no longer appropriate to contemporary life conditions (Item 4: write with a pencil someone else has obviously chewed on; Item 15: avoid using public telephones because of the risk that I may catch something from the previous use).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Items are scored on a 7point Likert scale, with endpoints labelled as "strongly disagree" and "strongly agree". The PVD has performed well on tests of reliability and validity (Duncan et al, 2009;Díaz et al, 2016;Magallares et al, 2017;Diaz, Beleña, & Zueco, 2020). In the present study, two items were excluded which appeared to be no longer appropriate to contemporary life conditions (Item 4: write with a pencil someone else has obviously chewed on; Item 15: avoid using public telephones because of the risk that I may catch something from the previous use).…”
Section: Methodsmentioning
confidence: 98%
“…Emotional and behavioral reactions in response to the threat of pandemic infections may be associated to the perception of personal risk to be infected, as well as aversion and discomfort in situations associated with increased risk of infection. Using the perceived vulnerability to disease scale (PVDS; Duncan, Schaller, & Park, 2009), significant correlations were found of the total score as well as both subscales, Perceived Infectability and Germ Aversion, with measures of health anxiety and hypochondriasis (Duncan et al, 2009;Díaz, Soriano, & Beleña, 2016), neuroticism (Duncan et al, 2009), negative attitudes towards people with HIV infection (Magallares, Fuster-Ruiz De Apodaca, & Morales, 2017) and towards people from East Asia during the COVID-19 pandemic (Goh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The current study used the following self-reported measurements: the perceived vulnerability to disease was assessed via the perceived vulnerability to disease scale validated in Spanish by Magallares et al 19 The scores of the participants were obtained by averaging their responses to the items on this scale. Higher scores indicated greater perceived vulnerability to infection.…”
Section: Instrumentsmentioning
confidence: 99%
“…Moreover, germ aversion is related to discomfort toward people with obesity and to a higher rejection to having physical contact with individuals with obesity (Park, Van Leeuwen, & Chochorelou, 2013). Recent research conducted with samples of teenagers (Magallares et al, 2015) and adults (Magallares, Fuster-Ruiz de Apodaca, & Morales, 2016) confirm that individuals who score high in a scale that measures germ aversion express more antifat attitudes.…”
Section: Germ Aversionmentioning
confidence: 88%